Manfaat Sari Kurma (Phoenix dactylifera L.) terhadap Peningkatan Hemoglobin Ibu Hamil: Analisis Tafsir Ilmi Kementerian Agama RI pada QS. Maryam/19:25-26 - Muhammad Ruslan; Moh. Samsul Ma'arif (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2026)
This study aims to analyze the benefits of date palm extract (Phoenix dactylifera L.) in increasing hemoglobin levels among pregnant women through an integrative approach between health science and the Tafsir Ilmi Kementerian Agama RI on QS. Maryam:25–26. Dates are known as fruits rich in iron, glucose, vitamins, and minerals that play an important role in supporting hemoglobin formation and preventing anemia in pregnant women. This research employed a qualitative method with a library research approach by analyzing Qur’anic verses, scientific exegesis, and health literature related to the benefits of date extract for pregnant women. The findings reveal that QS. Maryam:25–26 contains scientific indications regarding the importance of consuming dates as a source of energy and nutrition for women during pregnancy and childbirth. From the perspective of the Scientific Interpretation of the Indonesian Ministry of Religious Affairs, the command for Maryam to consume dates carries not only spiritual meaning but also health wisdom relevant to modern medical findings concerning hemoglobin improvement. Therefore, date palm extract has the potential to serve as a natural nutritional alternative in maintaining maternal health and preventing anemia during pregnancy.